Computational Design of Single Mo Atom Anchored Defective Boron Phosphide Monolayer as a High‐performance Electrocatalyst for the Nitrogen Reduction Reaction. Issue 2 (8th October 2020) - Liu, Zaichun; Huang, Ting; Chang, Huhu; Wang, Faxing; Wen, Juan; Sun, Haodong; Hossain, Masud; Xie, Qingji; Zhao, Yan; Wu, Yuping
Abstract : Catalytic reduction of molecular dinitrogen (N2 ) to ammonia (NH3 ) is one of the most important and challenging industrial reactions. Electrochemical reduction is considered as an energy‐saving technology for artificial ambient nitrogen fixation, which is emerging as an optimal potential sustainable strategy to substitute for the Haber–Bosch process. However, this process demands efficient catalysts for the N2 reduction reaction (NRR). Here, by means of first‐principles calculations, we systematically explored the potential electrocatalytic performance of single transition metal atoms (Pd, Ag, Rh, Cu, Ti, Mo, Mn, Zn, Fe, Co, Ru, and Pt) embedded in monolayer defective boron phosphide (TMs/BP) monolayer with a phosphorus monovacancy for ambient NH3 production. Among them, the Mo/BP exhibits the best catalytic performance for ambient reduction of N2 through the typical enzymatic and consecutive reaction pathways with an activation barrier of 0.68 eV, indicating that Mo/BP is an efficient catalyst for N2 fixation. We believe that this work could provide a new avenue of ambient NH3 synthesis by using the designed single‐atom electrocatalysts. Abstract : Electrochemical nitrogen reduction reaction is considered as an energy‐saving technology for artificial N2 fixation at ambient conditions. Here, the single Mo atom supported by the P‐vacancy defected BP monolayer is proved to be a promising single‐atom electrocatalyst for N2 fixation with a considerably small overpotential.